1982
DOI: 10.1093/ajcn/35.5.935
|View full text |Cite
|
Sign up to set email alerts
|

Dietary “meats” and serum lipids

Abstract: The mean values for serum total cholesterol for 47 males, aged 32 to 62 yr who, over a 10 1/2 month study ate, within a self-selected diet, beef as the only meat for 3 months, poultry and fish for 3 months, and pork for 3 months showed no statistically significant difference, whereas 17 of 29 females of the same age who participated in the same study had borderline statistically significant differences in mean values (p less than 0.055). When data from all subjects were considered together, no statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Throughout this study, as previously reported [13,23,24], not all changes from immediately previous blood values were in the same direction in the same person.…”
Section: Resultssupporting
confidence: 69%
See 4 more Smart Citations
“…Throughout this study, as previously reported [13,23,24], not all changes from immediately previous blood values were in the same direction in the same person.…”
Section: Resultssupporting
confidence: 69%
“…No significant changes in SCHOL, HDL-C, or STG were found in subjects eating food fats other than butter and margarine, such as beef, poultry/fish, and pork in a 10-month crossover design with humans consuming self-selected diets [23,24]. Reiser et al [54] studied beef fat vs coconut oil vs safflower oil incorporated into spe cial spreads, filled ice cream, and cookies, fed to human volunteers within their habitual foods taken ad lib for 5 weeks at a caloric level to maintain constant weight.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations